Systematic Specialist Lex Principle in Determining State-Owned Bank Employees as Suspects on Charges of Corruption - Azhar. AR; Mhd. Azhali Siregar; Suci Ramadhani (SEAN Institute, 2025)
Study This aiming for to study implementation lex specialis principle systematic in determination suspect state-owned bank employee who is suspected do act criminal corruption. In Indonesia, it often happen overlap overlap between provision Constitution Banking and Law Action Criminal Corruption, which gives rise to uncertainty law and differences judge's decision. Lex specialis principle systematic emphasize election provision more laws specific moment happen clash between law. Approach research used is legal normative with method descriptive analytical, relying on studies bibliography and analysis decision courts, including Decision Supreme Court Number 2405 K/ Pid.Sus /2016. Research results show that provision Constitution Banking should more prioritized in context banking, although there is inconsistency in its implementation by the authorities enforcer law. The need for strengthening understanding to principles law criminal special and application lex specialis principle systematic in a way consistent for ensure certainty law and justice in the sector banking.